2016
DOI: 10.1590/1413-2311.1622015.60360
|View full text |Cite
|
Sign up to set email alerts
|

CONEXÕES POLÍTICAS NAS MAIORES COMPANHIAS LISTADAS NA BM&FBOVESPA

Abstract: RESUMOAs conexões políticas podem ser caracterizadas como relações entre empresas e políticos, em que as empresas procuram obter vantagens e os políticos geralmente buscam financiamento de campanha. Nesse contexto, o estudo tem como objetivo geral analisar a relação entre as conexões políticas das maiores empresas listadas na BM&FBovespa e seus respectivos desempenhos. Para tanto, foram analisados os dados de 132 companhias, utilizando-se estatística descritiva, teste de diferença entre médias, Análise de Corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
1
8
0
3
Order By: Relevance
“…Political connections, according to Camilo et al (2012), may be characterized as relationships between political agents and companies, in which both seek to further their common interests. Thus, political connections are a practice that companies that depend on financial resources use to attain their objectives, seeking to expand their ties with politicians, who in turn are interested in the funding of their electoral campaigns (Pinheiro, Luca, & Vasconcelos, 2016). During recent decades, even though democracy and the economic system have evolved, mainly because of control mechanisms and the publication of public and private acts (Bazuchi et al, 2013), organizations need to diminish the uncertainties they face and increase their revenues to remain competitive, and thus they often use political connections to strengthen their ties to public agents (Brey, Camilo, Marcon, & Alberton, 2011).…”
Section: Theoretical Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Political connections, according to Camilo et al (2012), may be characterized as relationships between political agents and companies, in which both seek to further their common interests. Thus, political connections are a practice that companies that depend on financial resources use to attain their objectives, seeking to expand their ties with politicians, who in turn are interested in the funding of their electoral campaigns (Pinheiro, Luca, & Vasconcelos, 2016). During recent decades, even though democracy and the economic system have evolved, mainly because of control mechanisms and the publication of public and private acts (Bazuchi et al, 2013), organizations need to diminish the uncertainties they face and increase their revenues to remain competitive, and thus they often use political connections to strengthen their ties to public agents (Brey, Camilo, Marcon, & Alberton, 2011).…”
Section: Theoretical Referencesmentioning
confidence: 99%
“…They found that political connections are perceived by these analysts because of information published by the media in general, and that these connections influence the choice of maintaining or not maintaining a company with political connections in their investment portfolios. Pinheiro et al (2016) proposed analyzing the relationship between firms listed on the Bovespa Stock Exchange and political connections through their performance, and they found that there is no distinction in terms of performance when comparing firms with or without political connections.…”
Section: Theoretical Referencesmentioning
confidence: 99%
“…The second explanation offered by Chaney et al (2010) refers to the strength of the political connection that may provide a certain level of protection for connected firms, which would be exempt from punishment by inspection bodies and, thus, unconcerned about achieving better levels of QAI. In Brazil, this phenomenon was observed by Pinheiro et al (2016), who stated that political and democratic stability could discourage the harm caused by political connections by generating more costs than benefits. However, the authors observed that in developing economies, due to the difficulty in raising funds and reducing risks and uncertainties, firms may seek political connections as a solution.…”
Section: Introductionmentioning
confidence: 97%
“…Political connections occur through relations between companies and politicians and both of them aim their own interests (Pinheiro, Luca, & Vasconcelos, 2016). The companies, because of their dependence on resources, seek, through the signing of political ties, to satisfy their interests while protecting themselves from adverse scenarios that may modify the political connection established.…”
Section: Introductionmentioning
confidence: 99%
“…In the academic milieu, the political connection theme has been the recent target of several studies that have approached its relation with different variables, such as performance (Pinheiro et al, 2016), market value (Camilo, Marcon, & Bandeira-de-Mello, 2012b), analysts' perception (Macedo et al, 2015); property structure (Brey, Camilo, Marcon, & Alberton, 2011).…”
Section: Introductionmentioning
confidence: 99%